O ingresso da criança de seis anos no ensino fundamental de nove anos na perspectiva de professoras da rede estadual de ensino do Estado de São Paulo - Moraes, Milene Carla Rovaron (2014)
This study aims to understand the changes in the educational system from the Law 11.274/2006, which expanded elementary school for nine years duration including the entry of a child of six years , aiming to improve the equity and quality of basic education for children pursuing studies , achieving higher levels of education and to ensure that entering early, children have a longer time to the learning of literacy and literacy . Based on this assumption, the research aims to investigate, from the testimony of teachers , as is enabling the nine-year elementary school and entering the six year old in the first year at State Schools in the State of São Paulo . The survey was conducted with five teachers from the first year of elementary school in State Schools in the State of São Paulo and methodological option directed to the qualitative approach. We used semi-structured interview and, after collecting data using document analysis, characterization and interview subject, departed to the confrontation between these data to treat them and analyze them making this research relevant for studies in Education. Among the challenges mentioned by teachers are: the restructuring of the physical space to fit a child of six years; continuing education about the specifics of these children , as well as guidance on the use of teaching materials , the need to have an assistant professor class and reducing the amount of students per class. Therefore necessary to actualize what determines the Law 11.274/2006 changes are: partnership between ESS, managers and teachers in order to meet the needs of the school and the teacher feel supported to do their jobs; integration between school planning polyvalent teachers and specialists, that is, teachers of all disciplines and arts, and physical education, respectively, sufficient for teachers to maintain a decent standard of life and dedicate themselves only to the State Schools in the State of São Paulo remuneration